Effects of different substrates and selected feeds on the growth and survival of hatchery produced Penaeus monodon postlarvae - Martosudarmo, Budiono
A 4x2 factorial experiment in a completely randomized design (CRD) utilizing 24 units of 1x1x0.8 m3 suspension nets installed in a 500 sq m brackishwater pond was conducted at the UPVCF-Brackishwater Aquaculture Center, Leganes, Philippines. Fifteen-day-old hatchery-produced Penaeus monodon postlarvae were utilized in the experiment at a stocking density of 500 postlarvae per net. Four types of substrates (bamboo screened, plastic sheet, nylon screen and without substrate) and two kinds of food (lab-lab and mussel meat) were used as treatment replicated 3 times each to determine their effects on the growth and survival of postlarvae in 30 days. Water parameters such as salinity, temperature, pH, dissolved oxygen and ammonia were mentioned regularly. Results indicated no significant effect (P>0.05) of substrates on the growth of P. monodon postlarvae. However, a highly significant effect (P<0.01) on survival was observed. The survival of postlarvae differed significantly (P<0.05) in treatments provided with the various substrates than in those without substrates. No significant difference (P>0.05) in survival was noted among bamboo screen, plastic sheet or nylon screen substrates. The effect of the two food sources, lab-lab and minced mussel meat, on the growth of postlarvae during the first 20 days of rearing was not significant (P>0.05) indicating that these food sources were comparable. However, after 30 days of culture, growth was observed to be significant (P<0.05) which could be due to the difference in protein content between the two foods and the preference of the animals for mussel meat. The effect of the food types on the survival of postlarvae was not significant, although a significant interaction between feeds and substrates on the survival was observed.